The Influence of Electrode Impedance on the Parameters of Visual Evoked Potentials - Joanna Górecka (Applied Sciences)
The choice of a proper electrode is determined mainly by the type of examination. For recording spontaneous activity of the brain (EEG), two types of reusable electrodes should be considered, i.e., cup (Au, Ag, Ag/AgCl) and sintered bridge electrodes (SBEs) with a gold or silver pin. In the case of evoked potentials (EPs), only cup electrodes are used. To test the effect of electrode choice on the parameters of evoked potentials, twenty reusable electrodes of each type, i.e., Au, Ag, Ag/AgCl, were used to record visual evoked potentials (VEPs). The electrodes were then further tested by the electrochemical impedance spectroscopy (EIS) method. The presented research confirms the existence of an effect of the number of examinations performed with the same set of reusable cup electrodes on the values of the VEP parameters. A prolongation of the latencies and variability in the amplitudes for all the individual VEP components were observed. The obtained results suggest possible advantages of using reusable cup electrodes only once. An alternative to these electrodes may be solutions based on materials composed of polymers or dry electrodes.